«Sharing the Sun»: Activities that Move and Touch: Insights from Ethnographic Fieldwork at Day Care Centers for Older Adults in Norway - Holster, Terhi; Herholdt-Lomholdt, Sine Maria (Nordisk Tidsskrift for Helseforskning, 2025)
Day Care Centers (DCCs) for older adults living at home are widespread in Norwegian elderly care. However, the quality of provided services varies significantly between different municipalities and institution. One contributing factor to this variation may be the limited research on DCCs participants’ own experiences. This article is based on ethnographic fieldwork conducted at four DCCs, where participants have diverse background. The aim of the study is to gain deeper insight into the meaning that activities connected to nature or music may have for older adults. The findings, which indicate that nature and music have a vitalizing effect on older adults, are illustrated through concrete situation descriptions and discussed in the light of Martha Rogers’ theory of ‘Unitary Human Beings’ and Karin Dahlberg’s understanding of vitality from a lifeworld-oriented perspective.